Technical efficiency of fish farming by the DEA method in the northwest region of são paulo - Sabbag, Omar Jorge [UNESP]; Costa, Sílvia Maria Almeida Lima [UNESP]; Barroso, Renata Melon (My University, 2018)
Fish farming contributes positively to food production in the country and, with the expansion of crops, management in fish farms is essential. The objective was to analyze the technical efficiency of fish farmers in the Northwest region of São Paulo, as well as to investigate variables that affect their efficiency. Methodologically, to measure the efficiency scores, the non-parametric Data Envelopment Analysis (DEA) technique was used. In order to find the explanatory variables of efficiency, the econometric model Tobit was used. The results showed an average efficiency of 80% among the producers. As for the inefficient properties, 64% obtained increasing returns, being able to expand the production obtained. Characteristics such as collective organization, technical assistance and technology adopted tend to increase efficiency; the indebtedness is pointed as a factor that influences in a negative way the scores. It is concluded that the inefficiency pointed out in the fish farming of the region can be high with improvement in the management and technical and managerial training to the fish farmers.
Keywords: DEA analysis; Tilapia; Tobit model